Preparation and Evaluation of Liposomes and Niosomes Containing Total Ginsenosides for Anti-Photoaging Therapy - Jin, Yuanyuan; Liu, Da; Lu, Zhen; Yang, Lubing; Chen, Jiangli; Zhou, Xuyan; Qiu, Zhidong; Jin, Ye (Frontiers in Bioengineering and Biotechnology, 2022)
Ginseng saponins (GS) are the main bioactive substances of ginseng, with excellent anti-photoaging activity and improve the barrier function of skin. In order to enhance the efficiency of GS transdermal and absorption, GS liposomes (GSL) and GS niosomes (GSN) were prepared as delivery vehicles. Based on the clarified and optimized prescriptions, GSL and GSN were preparation, and then, the structure, cumulative transmittance, skin retention, and total transmittance of GSL and GSN were characterized. Moreover, the bioactivity of GSL and GSN were detected by indicated experiments. GSL and GSN can inhibit lipid peroxidation, increase the contents of uperoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and significantly promote the cellular uptake, migration and proliferation of HaCaT cells. Meanwhile, the therapeutic effects of GSL and GSN were also evaluated on rat photoaging model. The skin histopathological changes in rats treated with GSL, GSN, or GS were assessed by hematoxylin-eosin (H&E) and aldehyde fuchsine staining. Also, the expression levels of malondialdehyde (MDA), SOD, GSH-Px, matrix metalloproteinases (MMPs), interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α) in tissues were determined. The optimal formulation for GSL was as follows: soybean lecithin (SPC) was chosen as the phospholipid, the lipid-drug ratio was 1/0.4 and the ratio of phospholipid to cholesterol was 1/3.5. The optimal preparation process of GSN by ethanol injection was as follows: the temperature was 65℃, the ratio of organic phase to aqueous phase was 1:9. It is demonstrated that the cumulative release rate, skin retention rate and total transmission rate of GSL-7 at 24 h were higher than those of GSN-4 and GS. GSL-7 could significantly inhibit skin lipid peroxidation caused by ultraviolet radiation. Moreover, GSL-7 reduced the contents of matrix metalloproteinases and inflammatory factors in skin tissues. In conclusion, GSL-7 could effectively counter skin aging caused by ultraviolet radiation and repair skin tissue.